Pentingnya Legalitas Usaha dalam Mendorong Tertib Administrasi dan Transparansi Keuangan UMKM di Desa Waringin Jaya - Zhafira, puti; Pangaribuan, Laspita; Ekasakti, Yusvinora; Holiawati; Saga, Baharuddin (Abdimisi, 2025)
This Community Service activity aims to enhance the understanding and compliance of Micro, Small, and Medium Enterprise (MSME) owners in Waringin Jaya Village regarding the importance of business legality and proper administrative governance. The program was conducted through training sessions, assistance with administrative procedures, and the use of digital technology for online-based business licensing processes. A post-activity evaluation was carried out using structured questionnaires (post-tests) and in-depth interviews to measure the increase in participants' knowledge, shifts in perception, and their readiness to implement proper business legality practices. The evaluation results indicate that over 80% of participants showed significant improvement in their understanding of business legality concepts, the benefits of administrative compliance, and basic tax obligations. The comprehensive training and mentoring provided have strengthened the independence and sustainability of the MSMEs, while also supporting the development of a culture of financial transparency in Waringin Jaya Village. In the long term, this initiative is expected to foster a collective awareness of the urgency of business legality as a foundation for legal protection and business growth. Keywords: Legality, Administration, Transparency.